PERFORMANCE OF MODIFIED YSD-UNIB12 SOLAR DRYER FOR CLOTHES MATERIAL DRYING - Yuwana Yuwana; Bosman Sidebang; Evanila Silvia (Jurnal Agroindustri, 2013)
YSD-UNIB12 solar dryer has been modified its interior by replacing the trays with rail suitable for clothes hanger and size in order to be applied to dry clothes. The dryer had 3 x 6 m2 total area with about 300 pieces of clothes capacity. The dryer finishes drying of wet towel faster (about 12 hours) than that of sun drying (more than 18 hours). The dryer also completed drying of “batik” cloth comparable to that of sun drying (about 13 hours) and drying of singlet faster (12 hours) that of sun drying (13 hours). The modified YSD-UNIB12 resulted better quality of dry cloth and was ready to be adopted for drying clothes